Multiresolution Shape Codes with Applications to Image Retrieval - Biswas, Arindam; Bhowmick, Partha; Bhattacharya, Bhargab B. (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2008)
A novel technique on shape coding of an object in a binary digital image, based on the tight isotheticpolygonal covers of the object in a multiresolution background, is proposed. This technique would be useful in various analyses and applications related with digital images. To demonstrate the power and usefulness of such shape codes, we have also proposed an image retrieval scheme based on shape codes. The elegance of the scheme on shape codes lies in capturing the shape of the object(s) present in an image from its gross appearance to its finer details by a set of isothetic polygons, in a hierarchical manner. The inherent tolerance present in such a cast of isothetic polygonal shape enables the shape codes of two objects resemble closely as the grid resolution becomes finer and finer, provided the objects are of similar shapes. The method is very fast because it does not involve any complex computations, and requires only integer-based comparisons and additions. Experimental results demonstrate the strength and efficiency of the proposed scheme.